USING EXTENSIVE READING TO IMPROVE ECONOMIC VOCABULARY FOR SECOND-YEAR STUDENTS AT THE UNIVERSITY OF LANGUAGES AND INTERNATIONAL STUDIES – VIETNAM NATIONAL UNIVERSITY, HANOI - Phuong, Truong Thi (VNU Journal of Foreign Studies; Vol 34 No 4DO - 10.25073/2525-2445/vnufs.4289, 2018)
There are different ways to improve vocabulary knowledge and one of them is through extensive reading. This paper aims to identify benefits of extensive reading on some aspects of vocabulary learning and ways to conduct a successful extensive reading program. In order to answer the two research questions, the researcher collected and analyzed online journal articles which focus on the relationship between vocabulary development and extensive reading. The results show that extensive reading not only improves new vocabulary knowledge but also fosters previously met words. Moreover, some specific aspects of vocabulary learning are benefited thanks to extensive reading such as meaning, spelling and grammar. Finally, some recommendations on how to carry out an extensive reading are raised at the end of the result section based on various researchers’ opinions.